PENCEGAHAN PEMBUKAAN REKENING DALAM TINDAK PIDANA PENCUCIAN UANG PADA KANTOR CABANG SYARIAH BPD KALTIM - Agung Bhakti Hutomo (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT                This study aims to test empirically and find out how your account opening for the prevention of money laundering in the customer service unit at the Branch Office BPD Kaltim Samarinda. This study intends to find out how much tips and effort BPD Kaltim early Islamic prevent money laundering in particular of the earliest and small are in the process of opening an account to run the business - the dirty business of the perpetrators - perpetrator of money laundering (AML ). The research method that I use is empirical juridical sociological approach, the sampling method used by the writer is using purposive sampling technique. This research data retrieval technique using interviews, observation, and documentation. Type of interview used by the author is the semistructured interview. Method - the method of account opening made in the prevention of money laundering in the customer service unit must have been set in the applicable SOP, but of SOP is not enough, where power analysis or assessment conducted by the CS and Teller to each customer conducting transactions banking and menentukkan important enough. From this analysis to sharpen soul to the customer service -user user company is obliged to provide training - training with themes and new concepts related background mode - the mode abusing customers who bank savings account in conducting money laundering.Key word : Money Laundering